2021
DOI: 10.1021/acs.macromol.1c00885
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Design of Acrylates Containing Isocyanurate Moiety Undergoing Low Volume Shrinkage during Their Radical Photopolymerization

Abstract: A series of isocyanurate-based acrylates was successfully synthesized from tris­(2-hydroxylethyl) isocyanurate. Their radical photopolymerization under the irradiation of 365 nm smoothly proceeded to afford the corresponding oligomers in good yields. Volume shrinkage values during the radical photopolymerization of isocyanurate-based acrylates were much smaller than those of common acrylates and the comparative acrylates bearing no isocyanurate core. Interestingly, monofunctional acrylates consisting of three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 48 publications
2
9
0
Order By: Relevance
“…The calculation of volume change (Δ V ) was performed using the following equation: Δ V = (Density monomer − Density polymer )/Density monomer × 100. In the our previous report, [ 8 ] we found that 2a shows almost zero volume shrinkage and substantiated that the combination of the isocyanurate core and urethane bonds is effective in the suppression of volume change during the progress of polymerization. The densities of 2b–f containing aromatic moieties were much larger than that of 2a consisting of hexyl moieties (entries 1 vs 2–6), indicating that the introduction of the aromatic moieties inducing π – π interaction into the monomer molecule increases in the density of the monomer.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The calculation of volume change (Δ V ) was performed using the following equation: Δ V = (Density monomer − Density polymer )/Density monomer × 100. In the our previous report, [ 8 ] we found that 2a shows almost zero volume shrinkage and substantiated that the combination of the isocyanurate core and urethane bonds is effective in the suppression of volume change during the progress of polymerization. The densities of 2b–f containing aromatic moieties were much larger than that of 2a consisting of hexyl moieties (entries 1 vs 2–6), indicating that the introduction of the aromatic moieties inducing π – π interaction into the monomer molecule increases in the density of the monomer.…”
Section: Resultssupporting
confidence: 84%
“…In addition, the structures of 1b–f were determined by NMR (Figures S1–S5, Supporting Information), ESI (Figures S19–S23, Supporting Information), and IR (Figures S25–S29, Supporting Information) analyses. According to the our reported procedure for the synthesis of the acrylates 2a [ 8 ] and 2g , [ 9 ] we first carried out the reaction of 1b–f with 2‐ethyl acryloyl isocyanate in the presence of DBTDL as a catalyst in dichloromethane at 40 °C for 2 h under a nitrogen atmosphere, affording the corresponding acrylates 2b–f in reasonable yields (Scheme 1). The chemical structures of 2b–f were studied by NMR (Figures S6–S10, Supporting Information), ESI (Figures S19–S23, Supporting Information), and IR (Figures S25–S29, Supporting Information) analyses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that photo-polymerization and photo-crosslinking induce volume shrinkage, and attempt has been made to design network polymers with low volume shrinkage. [39][40][41] This supports our conclusion that photoresponsive micropatterning on PCEMA-g-PDMS films is attributed to a decrease in the free volume of PCEMA-g-PDMS resulting from photodimerization of the cinnamoyl groups. Thus, we can utilize volume shrinkage of polymer films to design photoresponsive films with micropatternable surfaces, although most studies have focused on the low volume shrinkage of polymers by photo-polymerization and photo-crosslinking.…”
Section: (3 Of 9) Wwwadvmatinterfacesdesupporting
confidence: 84%
“…We have previously substantiated that the isocyanurate core is useful for the development of functional polymers by synthesizing isocyanurate core-containing polymers showing much higher thermal properties 29−32 as well as monomers exhibiting a low volume change during their radical polymerization. 33,34 Those researches stimulated us to use the isocyanurate core without a conformational change as the scaffold of monomer for cyclopolymerization. We have focused on the isocyanurate core-based bifunctional monomers bearing a hydroxy group as shown in Figure 1, because the resulting polymers have rigid macrocyclic units in the main chain and many hydroxy groups as a reactive point in the side chains and can be applied to the development of high thermal polymer materials.…”
Section: Introductionmentioning
confidence: 99%